2011
DOI: 10.3748/wjg.v17.i6.766
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients at-risk for Lynch syndrome in a hospital-based colorectal surgery clinic

Abstract: A significant proportion of patients with CRC were at high risk for LS. Education and training of health care professionals are essential to ensure proper management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
1
9
0
2
Order By: Relevance
“…furthermore, our results may be more robust than expected owing to referral and selection biases, because we are a tertiary referral center with a likely higher-risk population, similar to the biases noted in the Brazilian coloproctology clinic study. 16 it is noteworthy that over 20% of our CRC patients who were determined to be at risk after initiation of the registry declined to proceed to genetic testing, likely further biasing our final results.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…furthermore, our results may be more robust than expected owing to referral and selection biases, because we are a tertiary referral center with a likely higher-risk population, similar to the biases noted in the Brazilian coloproctology clinic study. 16 it is noteworthy that over 20% of our CRC patients who were determined to be at risk after initiation of the registry declined to proceed to genetic testing, likely further biasing our final results.…”
Section: Discussionmentioning
confidence: 86%
“…a study from a Brazilian tertiary care outpatient coloproctology clinic found that of 212 CRC patients, only 17% had adequate family histories obtained and only 4% had been sent for genetic counseling, but over 50% were found to actually be at risk for ls when the charts were retrospectively reviewed and the families recontacted for their family history data. 16 similarly, a norwegian study of 562 CRC patients from 2 hospitals showed that only 4 patients were sent for genetic counseling despite at least 137 (24%) patients being at high risk on retrospective review, and more patients having insufficient data to assess risk. 5 as with these studies, our differences in the apparent at-risk patients between the 2006 retrospectively assessed time period before the registry creation and the prospectively assessed period from 2007 to 2010 are likely explained by the inadequacy of family history assessment in the earlier time period.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Das höchste KRK-Risiko besitzen Männer mit defektem MLH1 oder MSH2 (80% bis zum Alter von 70 Jahren). In sämtlichen Studien [12][13][14] haben Frauen ein geringeres KRK-Risiko als Männer.…”
Section: Klinische Aspekteunclassified
“…14,15 several studies have recommended improving adherence to the Bethesda guidelines in patients with CRC, because better adherence could improve the identification of patients and family members with lynch syndrome. [16][17][18][19] this is important because the cumulative risk of metachronous CRC in patients with lynch syndrome is high (approximately 16% at 10 years, 41% at 20 years, and 62% at 30 years), and, thus, frequent colonoscopic follow-up after segmental resection is warranted. 20 in addition, it has been shown that colonoscopy every 1 to 2 years starting at the age of 20 to 25 years in mutation carriers largely reduces the incidence and mortality of CRC.…”
mentioning
confidence: 98%